2007
DOI: 10.1080/10408390600695300
|View full text |Cite
|
Sign up to set email alerts
|

Olive Oil Waste Treatment: A Comparative and Critical Presentation of Methods, Advantages & Disadvantages

Abstract: Since olive oil industries were considered responsible for a great amount of pollution there has been a strong need for optimization of olive oil waste treatment systems. The currently employed systems are numerous and fall in the following large categories; bioremediation (ex-situ, in-situ), thermal processes (incineration, pyrolysis, gasification), evaporation, membrance processes, electrolysis, ozonation, digestion, coagulation/flocculation/precipitation, and distillation. Both advantages and disadvantages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 99 publications
1
35
0
5
Order By: Relevance
“…Studies in this regard pertaining to olive oil (Arvanitoyannis and Kassaveti, 2007;Arvanitoyannis et al, 2007aArvanitoyannis et al, , 2007bVlyssides et al, 2004), castor oil (Sivakumar et al, 2008) and palm oil (Reijnders and Huijbregts, 2008) have been reported earlier. Recently, production of bioparaffins by the catalytic hydrogenation of natural triglycerides (Hancsók et al, 2012) and sustainability and mitigation of greenhouse gases using ethyl beef tallow biofuel in energy generation (Pereira et al, 2012) have been reported.…”
Section: Oils/fats Treatment Processesmentioning
confidence: 92%
“…Studies in this regard pertaining to olive oil (Arvanitoyannis and Kassaveti, 2007;Arvanitoyannis et al, 2007aArvanitoyannis et al, , 2007bVlyssides et al, 2004), castor oil (Sivakumar et al, 2008) and palm oil (Reijnders and Huijbregts, 2008) have been reported earlier. Recently, production of bioparaffins by the catalytic hydrogenation of natural triglycerides (Hancsók et al, 2012) and sustainability and mitigation of greenhouse gases using ethyl beef tallow biofuel in energy generation (Pereira et al, 2012) have been reported.…”
Section: Oils/fats Treatment Processesmentioning
confidence: 92%
“…An understanding of the variation of pH with addition of fl occulants/coagulants/precipitants is essential because of its effects in the water treatment process [20]. From Fig.…”
Section: Effect Of Fl Occulant/coagulant/precipitant On Solution Phmentioning
confidence: 99%
“…However, they both require long treatment times for satisfactory results (Arvanitoyannis et al, 2007;Jarboui et al, 2010). The use of tree-based phytoremediation to treat and dispose OMW may represent a viable in-between option since it allows to stimulate bioremediation at the root level and to accelerate evaporation due to leaf evapotranspiration (Alkorta and Garbisu, 2001).…”
Section: Factors Affecting Phytoremediationmentioning
confidence: 99%